2018
DOI: 10.6087/kcse.116
|View full text |Cite
|
Sign up to set email alerts
|

Authors’ perspectives on academic publishing: initial observations from a large-scale global survey

Abstract: Authors are at the heart of academic publishing, but their voices are underrepresented in discussions about improving the academic publishing system. To understand the viewpoints of authors on various aspects of academic publishing and the challenges they face, we developed a large-scale survey entitled "Author perspectives on the academic publishing process" and made it available in December 2016. The survey has received 8,795 responses; this paper is based on the interim results drawn from 5,293 survey respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
0
11
1
1
Order By: Relevance
“…Participants reported the greater likelihood of being published and support of smaller, singleinstitution studies as factors as well. This differs from a broad survey conducted by Souza (Editage Insights, 2018;Souza et al, 2018) that reported the impact factor of a journal to be the most prominent consideration for journal selection.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Participants reported the greater likelihood of being published and support of smaller, singleinstitution studies as factors as well. This differs from a broad survey conducted by Souza (Editage Insights, 2018;Souza et al, 2018) that reported the impact factor of a journal to be the most prominent consideration for journal selection.…”
Section: Discussioncontrasting
confidence: 68%
“…guidelines and standards (Solomon, 2014;Souza et al, 2018). Additional publication-related surveys have addressed attitudes toward open access, difficulty with manuscript preparation, and a more global assessment of the peer review and publication process itself (Editage Insights, 2018).…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por el contrario, en el estudio de D´ Souza y colaboradores indicaron que existe una necesidad de hacer el proceso de publicación más amigable, para evitar la brecha entre la comunicación entre el autor y la revista. 19 En este sentido es fundamental que la RMH mantenga y fortalezca la asesoría personalizada con los autores. La necesidad de asesoría personalizada se hizo evidente en un alto porcentaje del grupo, tanto de autores como revisores y como refiere la investigación realizada por la revista "Investigación en Educación Médica" PROCESO EDITORIAL REVISTA MÉDICA HONDUREÑA DOI: https://doi.org/10.5377/rmh.v89i2.13020 editada por la Facultad de Medicina de la Universidad Nacional Autónoma de México en un grupo de revisores para conocer sus percepciones y experiencias en torno al proceso de revisión por pares, todos los participantes refirieron no haber recibido entrenamiento o capacitación específica para revisar artículos y, si bien la experiencia profesional es lo que expresaron como principal estrategia para la evaluación.…”
Section: Discussionunclassified
“…The other consideration is how fast the manuscript can be published. A survey was carried out in India to determine what authors thought about the academic publishing system and what would be the decisive factors in selecting a journal 6 . The survey results revealed that both impact factor and timeliness of the publication are among the first two aspects which influence the decision of selecting a journal.…”
Section: About the Journalmentioning
confidence: 99%